2017
DOI: 10.21859/ijpn-05032
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Caregiver Burden, and Depression, Anxiety and Stress in Family Caregivers of Cancer Patients Referred to Imam Reza Hospital in Bojnurd City

Abstract: Introduction: Cancer and its complications are not limited to the patients and affect their caregivers. The aim of this study was to determine the relationship between the caregiver burden, and stress, anxiety, and depression in these patients. Methods: In this cross-sectional study, 100 caregivers of cancer patients referred to the Imam Reza Hospital in Bojnurd City were selected through the convenience sampling method. The data instruments included the caregiver burden questionnaire and depression, anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
0
13
1
Order By: Relevance
“…96.6% of the caregivers had a high school diploma or a lower education level. Safaeian [ 39 *] 2017 100 Cancer CBI 77.56 Gender of the patients: 55 women and 45 men Mean age of the caregivers: 38.1 ± 12.5 years Gender of the caregivers: 58 women and 42 men 64% of the caregivers were children of patients. 43% of the caregivers had primary school education.…”
Section: Resultsmentioning
confidence: 99%
“…96.6% of the caregivers had a high school diploma or a lower education level. Safaeian [ 39 *] 2017 100 Cancer CBI 77.56 Gender of the patients: 55 women and 45 men Mean age of the caregivers: 38.1 ± 12.5 years Gender of the caregivers: 58 women and 42 men 64% of the caregivers were children of patients. 43% of the caregivers had primary school education.…”
Section: Resultsmentioning
confidence: 99%
“…Safaeian et al (2016) found that more than half of caregivers of cancer patients experience severe and very severe CB levels. They also confirmed that it seems necessary to evaluate primary caregivers by members of the treatment team and develop family-centered rehabilitation programs [18]. Therefore, it is necessary for mothers to have a good mood in order to be able to adequately adapt to the disease.…”
Section: Introductionmentioning
confidence: 68%
“…Family members are most involved in caring for the patient, helping her to adapt and manage the condition [4]. However, increasing pressure on caregivers will have several consequences, such as inadequate patient care, patient abandonment, family isolation, despair, and restraint of family relationships [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as caregivers spend most of their time with the patient, they often forget about their needs. Cancer affects the whole family [4]. They may experience economic, social, physical, psychological, and spiritual problems [6,7].…”
Section: Introductionmentioning
confidence: 99%